PENGARUH PENERAPAN PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BERDASARKAN TEORI POLYA SISWA KELAS XI SMAN 1 KALIDAWIR TULUNGAGUNG - Heritin, Anisak; Salamah, Nikmatus (TARBAWI:Journal on Islamic Education, 2023)
The aim of this research is to determine the influence of the application of problem solving learning on mathematical problem solving abilities based on polya theory, and to determine the magnitude of the influence of the application of problem solving learning on mathematical problem solving abilities based on polya theory of class XI students at SMAN 1 Kalidawir. This research uses a quantitative approach with quasi experimental design (post-test only). The sample was selected using purposive sampling technique. The data collection techniques used were observation, tests and documentation. The research results showed that the average posttest score for problem solving ability in the experimental class was 70.94 and in the control class 51.47. The results of the t-independent sample test show that the Sig (2-tailed) value is 0.000 0.05, so H_α is accepted and H_0 is rejected. Based on the research results, it is also known that the value of t_0 or t_count = -4.714 with db or df = 59. The effect size value or the proportion of variance obtained is classified as a large effect. So it can be concluded, there is an influence of the application of the problem solving learning model on mathematical problem solving abilities based on POLYA theory and the large influence of the application of the problem solving learning model on mathematical problem solving abilities based on POLYA theory of class XI students at SMAN 1 Kalidawir Tulungagung is classified as a large effect.